Decentering the researcher in intimate scholarship : critical posthuman methodological perspectives in education - Strom, Kathryn J.; Mills, Tammy; Ovens, Alan (Bingley, U.K. : Emerald Publishing Limited, 2018)
"Intimatescholarship" refers to qualitative methodologies, such as self-study and autoethnography, that directly engage the personal experience, knowledge, and/or practices of the researcher(s) as the focus ofinquiry. While intimate scholarship offers entry points into non-binary thinking by blurring the line between researcher/researched, much work in this genre continues to reinforce a humanist "I". In this volume, we ask what happens when the researcher in forms of intimate scholarship is decentered, or is considered as merely one part of an entangled material-discursive formation. Chapters in this volume highlight ways that researchers of teaching and teacher education can advance conversations in education while exploring theories with an ontological view of the world as fundamentally multiple, dynamic, and fluid. Drawing on a range of methods, authors "put to work" posthuman, non-linear, and multiplistic theories and concepts to disrupt and decenter the "I" in intimate methodologies. Also featured in this volume are conversations with leading posthuman scholars, who highlight the possibilities and challenges of decentering the researcher inintimate scholarship as a practice of social justice research.
Prelims -- Introduction: decentering the researcher in intimate scholarship -- Affective reverberations: the methodological excesses of a research assemblage -- Teaching in, relating in, and researching in online teaching: the desiring cartographies of two second language teacher educator becomings -- We, monsters: an autoethnographic literature review of experiences in doctoral education programs (Kind of) -- Decentering the "self" in self-study of professional practices: a working research assemblage -- New materialist auto-ethico-ethnography: agential-realist authenticity and objectivity in intimate scholarship -- Narrative mining: story, assemblage, and the troubling of identity -- The luxury of vulnerability: reflexive inquiry as privileged praxis -- The rhizomes of academic practice: culturally and linguistically diverse students negotiating learning and belonging -- Pedagogy, naked and belated: disappointment as curriculum inquiry -- Art as a "thing that does": creative assemblages, expressive lines of flight, and becoming cosmic-artisan in teacher education -- Becoming-with/in educational research: minor accounts as care-full inquiry -- Affirmative ethics, posthuman subjectivity, and intimate scholarship: a conversation with Rosi Braidotti -- Decentering subjectivity after Descartes: a conversation with Michael Peters -- Encounters and materiality in intimate scholarship: a conversation with Maggie MacLure -- Deleuzo-Guattarian decentering of the I/eye: a conversation with Jessica Ringrose and Shiva Zarabadi -- About the Authors -- Index.
Includes index.
Print version record
Keywords: Teaching -- Research; Teachers -- Training of -- Research; Qualitative research; Education, Professional Development; Teaching skills & techniques